A Note on \(q\)-Sălăgean Type Functions (Journal of Informatics and Mathematical Sciences, 2025)
In the present paper, we define certain classes of analytic function in the open disc by using the generalized linear operator \(D_{λ,δ}^{n}\) with help of \(q\) calculus. For functions belonging to these classes we provide coefficient inequalities, distortion theorem.